How we think : a theory of goal-oriented decision making and its educational applications - Schoenfeld, Alan H. (Studies in mathematical thinking and learning, 2011)
Teachers try to help their students learn. But why do they make the particular teaching choices they do? What resources do they draw upon? What accounts for the success or failure of their efforts? This title proposes a theory and model for how we think and act in the classroom and beyond